If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8x+4(x-7)=12
We move all terms to the left:
-8x+4(x-7)-(12)=0
We multiply parentheses
-8x+4x-28-12=0
We add all the numbers together, and all the variables
-4x-40=0
We move all terms containing x to the left, all other terms to the right
-4x=40
x=40/-4
x=-10
| 2+2x-8x=6+10-x | | 79=0.1d+77 | | 0.3x+3.6=9.9 | | 1+4n=n-4-5-5 | | 6+7n=55 | | 3x+x-8=20 | | 9=k-3-4k | | x+0.1x=206972 | | 6(y+8)=6(y+8 | | 0.02x+2.4=2 | | 100-7x=4x+1 | | 2y÷5-3=10 | | -5/6k=-10/1 | | 8x-1=8(x-6) | | 3/4+n=1/2 | | x+0.1x=2077 | | 10x+5=3(5x+6) | | 9-(2n-3)=4-3n | | x-62=5 | | 7x+11=35-3x | | x-2.3=15.05 | | x–2.3=15.05 | | -42+x=-21 | | 7(2+w)=65(5+w) | | 53+y=72 | | 5x-10=x+20, | | 4x÷7=24 | | 3(5x+9)=162 | | 2x+7/6+x+8/6=x+7/4 | | F(x)=2x+3/4x4+9 | | 14k2-67k+63=0 | | 8.2z=24.6 |